PEMEROLEHAN FONOLOGIS ANAK USIA 3 TAHUN 3 BULAN SAMPAI 3 TAHUN 5 BULAN MELALUI LAGU (STUDI KASUS PADA MUHAMMAD ZAINI) [The Phonological Acquisition of Children Aged Three Years and Three Months to Three Years and Five Months through Songs (Case Study on Muhammad Zaini)] - Muhammad Rafiek (SAWERIGADING, 2019)
AbstractThis research aims to find out the phonological acquisition in the form of vowels and consonants on Muhammad Zaini from three years and three months to three years and five months. The theory used in this research is the universal structural theory of Jakobson and the theory of phonological acquisition from Moskowitz. The second theory also supported by findings of Dardjowidjojo (2000 and 2003). Analytical techniques used in the research were a longitudinal approach with engineering watch and note. The findings of this research were: (1) Muhammad Zaini acquired syllables in pronouncing a syllable /po/song delicious noodle advertisements on television. (2) Muhammad Zaini acquired phoneme /n/, /a/, /p/, /u/, /i/, /m/ in pronouncing the song of Nona Manis. (3)Muhammad Zaini obtained the letters A /a/, B /b/, C /c/, D /d/, E /e/, H /h/, J /j/, and O /o/. Muhammad Zaini was already able to pronounce the letter /u/, /p/, /q/, /v/, /w/ and /z/ in the alphabet. (4) Muhammad Zaini acquired phonological acquisition in the form of the letter get/p//a/,,/d/,/i/, u,/l/,/n/,/h/,/y/,/t/,/m/,/e/,/c/,/j/,/k/, in pronouncing the song of Pergi Pagi Pulang Pagi. AbstrakPenelitian ini bertujuan untuk menemukan pemerolehan fonologis berupa huruf vokal dan konsonan pada Muhammad Zaini dari usia 3 tahun 3 bulan sampai 3 tahun 5 bulan. Teori yang digunakan dalam penelitian ini adalah teori struktural universal dari Jakobson dan teori pemerolehan fonologis dari Moskowitz. Kedua teori ini juga didukung dengan temuan Dardjowidjojo (2000 dan 2003). Teknik analisis yang digunakan dalam penelitian ini adalah pendekatan longitudinal dengan teknik simak dan catat. Temuan penelitian ini adalah (1) Muhammad Zaini memperoleh suku kata /po/ dalam melafalkan lagu iklan mie sedap di televisi. (2) Muhammad Zaini memperoleh fonem /n/, /a/, /p/, /u/, /i/, /m/ dalam melafalkan lagu Nona Manis. (3) Muhammad Zaini memperoleh huruf A /a/, B /b/, C /c/, D /d/, E /e/, H /h/, J /j/, dan O /o/. Muhammad Zaini sudah mampu melafalkan huruf /u/, /p/, /q/, /v/, /w/, dan /z/ dalam abjad yang dilagukannya, dan (4) Muhammad Zaini mendapatkan pemerolehan fonologis berupa huruf /p/, /a/, /d/, /i/, /u/, /l/, /n/, /h/, /y/, /t/, /m/, /e/, /c/, /j/, /k/ dalam melafalkan lagu pergi pagi pulang pagi.